Politik Pengelolaan CSR PT. Bangka Asindo Agri di Kelurahan Kenanga Kabupaten Bangka: Desain dan Tantangan Implementasi - Pradina, Puput; Sarpin, Sarpin (Indonesian Democracy Research Center, 2023)
PT. Bangka Asindo Agri (BAA) located in Kenanga Village, Bangka Regency, Bangka Belitung Island Province from July 2022 until November 2022. This study used a descriptive qualitative research design with primary data and secondary data collected through observation, interview, and archived documentation. This data were analyzed using interactive model data analysis techniques from Miles and Hubberman. The result of this study indicate that: 1) CSR program design carried out by PT. Bangka Asindo Agri shows the government’s involvement with the company and the company’s involvement with the community in Kenanga Village, Bangka Regency can be said too poor; and, 2) Implementation of the CSR program from PT. Bangka Asindo Agri is carried out in accordance with Law Number 40 of 2007 concerning Limited Liability Companies, although it is not optimal. The implementation of CSR is influenced by inhibiting factors and driving factors.